Cluster-based pre-scaling up of improved faba bean variety technology demonstration at Arsirobe District of Arsi Zone, Oromia Regional State, Ethiopia - Sintayehu Abebe; Lemlem Abebe (Open Journal of Plant Science - Peertechz Publications, 2021)
Large Scale Demonstration (LSD) of Faba bean was conducted at Arsi robe district of Oromia regional state of Ethiopia. The district was selected due to its potential for Faba bean production. One cluster was formed in collaboration with district level agricultural experts.Generally the cluster size covered 4.6 hectares of land. A Faba bean varity called "Ashebeka" was demonstrated along with its full-recommended packages. Training were given for a total of 46 participants (39 farmers, 3 DAs and 4 SMS) at different stage on agronomice practice of Faba bean and chemical applications. To raise farmer's awareness on the performance of the Faba bean techinologies, a field day was organized and by this field day, a total of 74 participants were attended the field events (59 farmeres, 7 Experts and DAs and 5 distinguished guests were attened the events). From the varity demonstrated at study district the variety was acceptable during field visit and field day by farmers due to its disease tolerant and well adaptation and its productivity after harvesting (the varity has a yield advantage overe the Ethiopial national average yield of fababean (21quintals per hectare CSA 2020 and "Ashebeka"; Avarage Yield=30.2; quintals per hectare was recorded in the study area.